Estudo técnico ambiental como pressuposto para a regularização fundiária urbana em área de preservação permanente: Lei Federal n. 13.465 de 2017 - REURB - Silva, Tatiana Monteiro Costa e (2022)
This thesis was based on the unprecedented, current and necessary approach to urban land regularization in a permanent preservation area, after the edition of the innovative Federal Law No. 13.465 of 2017, self-declared Reurb, which established as a legal assumption the requirement for prior environmental study in consolidated informal urban centers totally or partially inserted in permanent preservation areas for land regularization purposes. The environmental technical study must be approved within the scope of the urban land regularization project and the guidelines of articles 64 of Federal Law no. 12.651 of 2012 (land regularization of social interest – Reurb-S in APP) will be observed, as well as in the situations of article 65 of Federal Law no. 12.651 of 2012 (land regularization of specific interest – Reurb-E in APP). Considering this analysis, the contextualization of the urbanization process in the country was sought mainly as a result of the rural-urban migration and the informal and illegal production of urban space from clandestine occupations which triggered the land, environmental, social and economic disruption. Add to this, the inefficient housing programs managed and coordinated by the Union over decades, as well as the marked omission of the public power in the deficient supervision or even its omission of new unwanted occupations of environmentally protected spaces, such as the permanent preservation area. The urban chaos experienced mainly by the poorest people gave rise to a fundamental subjective right to the existential minimum of decent housing, even if inserted in informal urban centers located in areas of permanent preservation. To this end, Federal Law no. 13.465 of 2017 enshrines the environmental technical study as a strategic environmental preventive instrument for the management of environmental regularity as an assumption for the urban land regularization of consolidated informal urban centers totally or partially located in a permanent preservation area